Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12936-017-1870-4
|View full text |Cite
|
Sign up to set email alerts
|

Malaria prevalence in asymptomatic and symptomatic children in Kiwangwa, Bagamoyo district, Tanzania

Abstract: BackgroundMalaria prevalence continues to decline across sub-Saharan Africa as a result of various intervention strategies. However, the diseases still poses a public health concern in the region. While symptomatic malaria is recognized and treated, asymptomatic infections become increasingly important for interrupting transmission. A cross-sectional survey was conducted to assess malaria prevalence in symptomatic and asymptomatic children in Kiwangwa ward in Bagamoyo District in Tanzania.MethodsFour hundred s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 31 publications
8
53
8
1
Order By: Relevance
“…However, this figure is lower than previous studies in Kenya 12.6% (28) and Tanzania 8% (29). Lower findings than the current study were reported in Malo, Southwest Ethiopia with no case (17), Myanmar 1.4% (30), and Haiti with 2.8% (24).…”
Section: Discussioncontrasting
confidence: 94%
“…However, this figure is lower than previous studies in Kenya 12.6% (28) and Tanzania 8% (29). Lower findings than the current study were reported in Malo, Southwest Ethiopia with no case (17), Myanmar 1.4% (30), and Haiti with 2.8% (24).…”
Section: Discussioncontrasting
confidence: 94%
“…Using microscopy in the current study, the overall prevalence of malaria was lower compared to RDT. is is consistent with recent studies by Sumari et al [11] and Huang et al [21] but contrary to results of a study in Myanmar where microscopy produced a higher prevalence than RDT [22]. e microscopic prevalence found in this current study is far lower than the 56% reported in 2010 and 27.5% in 2017 during a similar dry season study in the northern part of Ghana [18,23].…”
Section: Discussionsupporting
confidence: 90%
“…Individuals with asymptomatic infection carry very low parasite densities for extended periods and usually go untreated. As such, they contribute to malaria transmission especially in areas with seasonal transmission by serving as Plasmodium reservoirs [10][11][12]. Identifying and eliminating these reservoirs (through chemopreventive methods like mass drug administration) therefore will play a critical role in the fight against malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Probing further into the practices of the study population (which is outside the scope of this present study) would have revealed if drugs were used prior to hospital visitation and as such substantiate the claim of drug reaction on the parasite. Other studies showing same trend of lower prevalence by microscopy as against RDT where both were used include that carried out in Lagos, Nigeria (Olusegun-Joseph et al, 2016) and also in Tanzanian, though among children (Sumari et al, 2017). Such results however need validation by PCR in order to ascertain the true diagnostic status of the individuals.…”
Section: Discussionmentioning
confidence: 99%